Eksistensi Karanu Ghule pada Masyarakat Desa Lakarama Kecamatan Towea Kabupaten Muna - Saldin S; Rahmat Sewa Suraya; Agus Rihu (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2024)
Karanu ghule is a tradition that has been carried out for generations by the people of Lakarama Village because it is a tradition that is considered important and accepted by people who currently adhere to animistic beliefs. According to Karanu ghule, there was no objection from the local community because whatever tradition is considered for the community, it is mandatory to carry it out. The purpose of this study was to find out the process of implementing the Karanu ghule Mantra in the Lakarama village community, the function of the Karanu Ghule Mantra and the symbolic meaning of the Karanu ghule Mantra in the people of Lakarama Village, Towea District, Muna Regency. The method used in this research is Qualitative Research. Data collection was carried out using observation techniques (observation), in-depth interviews and documentation. Informat determination technique in this study used a purposive sampling technique. Data were analyzed using the following techniques: data collection, data reduction, data presentation and conclusion. The results of the study show that in the Karanu ghule Process there are several stages, namely, the preparatory stage, the implementing stage, the function of Religion functions as a relationship between God and humans so as to gain experience by using the ancestral personality which is described metaphorically in religious norms, rituals, and myths , and the function of protection is to avoid theft in the garden when leaving the garden to carry out activities outside or while traveling far away, while the symbolic meaning, Symbolic Meaning of Patida (Gembilang) Symbolic Meaning of Ghunteli (Egg) Symbolic Meaning of Ghue (Rattan) Symbolic Meaning of Botolo bhe oeno (bottle filled with water).